Chiri Wayrita: La Voz de los sin voz. Una Experiencia de Educación Transformadora Para los Niños y Niñas del Cerro Rico (Bolivia). - Mara García Rodríguez,; Dolores Fernández Malanda, (Global Journal of Human-Social Science, 2021)
For a decade the University of Burgos through the Vice-Rectorate for Internationalization and Cooperation and the Center for Cooperation and Solidarity Action is committed to a series of educational and health projects in Bolivia specifically in the Department of Potos Throughout these years students and teachers of different degrees have participated in an experience that has changed our worldview by approaching cultures that survive individualism reification and depersonalization pillars of wild neoliberal capitalism empowering and strengthening the feeling of community Living with the Andean Quechua and Aymara peoples participating in their own education models in schools as complex and beautiful as Robertito built in the heart of one of the most terrible mines on the planet the Sumaq Orcko has made us acquire a new and enriching vision of the world from a worldview revealing to us by the principles of solidarity and reciprocity upon which it has been built Fern ndez Malanda D in Cifuentes Garc a and G mez Campelo 2016 121